Effects of acute weight loss on serum mineral homeostasis in elite male judoka - Burcu Yenturk; Mihrac Koroglu; Nuri Muhammet Celik; Cuneyt Sensoy; Fıkret Soyer (Journal of Men's Health, 2025)
Background: Acute weight loss practices among judoka, typically aimed at qualifying for a lower weight class to gain a competitive advantage, may pose significant health risks. Maintaining optimal serum mineral levels is critical for both physiological function and athletic performance. This study aimed to examine the effect of acute weight loss on serum mineral concentrations in elite male judoka. Methods: The study included 32 elite-level male judoka who were participating in the Turkish Judo Championship and were selected through convenience sampling. Among these athletes, 15 individuals who engaged in rapid weight loss were assigned to experimental group, while the remaining 17 athletes who did not undergo weight reduction were assigned to control group. Demographic data, including age, height, and training experience, were collected using standardized forms. Body weight and venous blood samples were obtained at two time points: one week and one day prior to the competition. Weight, body mass index (BMI), and serum concentrations of sodium, potassium, calcium, magnesium, and chloride were analyzed. Paired Samples T-Test and Independent Samples T-Test were utilized to assess within-group and between-group differences, respectively. Results: In the experimental group, post-test values demonstrated a statistically significant increase in serum sodium levels (p < 0.05), along with notable decreases in magnesium and chloride concentrations (p < 0.05). No significant changes were detected in the other serum minerals within the experimental group or in any parameter among the control group. Moreover, post-intervention sodium levels were found to be significantly higher in the experimental group when compared to the control group (p < 0.05). Conclusions: Acute weight loss results in measurable alterations in specific serum mineral levels among elite male judoka, emphasizing the potential health risks of rapid weight reduction strategies in high-level competitive sports. These findings underscore the need for evidence-based guidance on weight management practices among athletes.